Implement solar powered notenook - Siti Norfarha, Jumaat (2012)
A notebook integrates most of the typical components of a desktop computer, including a display, a keyboard, a pointing device (a touchpad, also known as a track pad, and/or a pointing stick) and speakers into a single unit. A notebook can be used away from an outlet using a chargeable battery. Usually, notebook is powered by AC supply from single phase 240V. When the notebook is depending on the AC supply, it cannot recharge whenever in rural area where there is no AC supply. In this project, the solar powered notebook that implement solar energy is represented in order to give supply to a notebook. The solar notebook concept is a laptop with complete power independent. This is due to powerful batteries that are recharged by any solar panel attached to the computer. The solar panel that attached to the notebook is able to convert solar energy to DC power that can give power to the notebook. It is expected that the notebook can switch on without AC power as it energized by solar energy.